Programa De Psicomotricidad En Niños De 7 A 9 Años De La Escuela Maes Sport De Baloncesto De La Cuidad De Armenia (2014)
The present project consisted of realizing an intervention by means of a program of psychomotor activity in 7-9-year-old children in the school Maes Sport, with the aim (lens) to promote the practice of the basketball, In the first instance (authority) there were controlled failings found in a work named psychomotor profile of the schools of the IMDERA of her (it) Take care of Armenia, which (who) was realized by Arias and Bolivar (2011), the opposing failings were: Balance, Praxia Global, Structure temporary Space, Notion of the Body, From the results of this study executed the program of psychomotor activity here present. Also one sought to develop skills psicomotrices, by means of played forms, game, didactics, creativity, all this by means of the recreation In order which the child in the practice of the basketball in ages of 7-9 years before beginning the technical development of tactical foundations has a process of development psicomotriz where by means of methodological and didactic processes it(he, she) experiences royal(real) situations of game that it(he, she) will allow him(her) with facilitate to acquire Skills in his (her, your) movements and for ende in the failings mentioned previously. The used methodology was of direct intervention with a population of 15 children approximately between 7-9 years of age it was possible to conclude that the psychomotor activity is fundamental in the sports initiation and more even in the ages initiate them, before developing technical foundations - tactical and working from this approach maybe facility is obtained more in the learning.